Most Common Errors in Students’ Narrative Writing: A Study of First-Grade SMS 70 Use of the Simple Past Tense - Fadhillah, Rastia; Mutiarani, Mutiarani (British (Jurnal Bahasa dan Sastra Inggris), 2024)
This study looks into the most common errors made by students in first grade at SMA 70 when writing narratives, particularly when using the simple past tense. To look into and analyze the mistakes made by the students, the study uses a qualitative descriptive methodology. Samples of first-grade student' narrative writing were used to gather data. The investigation found that 67% of all errors were caused by misformation through analysis. These grammatical mistakes reveal a lack of knowledge and expertise in employing the proper forms of the simple past tense. The results of this study provide information about the precise areas in which students have difficulty when writing narratives, particularly when it comes to verb tense. By being aware of these typical mistakes, teachers can create specific instructional strategies to aid students in developing their narrative writing abilities and advancing their command of the simple past tense.